Effectivity of Model Project Based Learning (PjBL) Type Make Crossword Puzzle Project to Improve 5th Grade Elementary Student’s Collaboration Skills - Pratama, Sapikzal; Agustin, Mubiar; Ardiyanto, Eko (International Conference on Elementary Education, 2022)
Project Based Learning (PjBL) Model was assumed less popular for elementary teacher to use because ineffectively. Though teacher seldom used it in class. This research aimed to know how effective PjBL type crossword puzzle project to improve student collaboration. The Method was descriptive qualitative. Data was collected by student’s peer rating and observing student’s collaboration on PjBL of 27 students at 5th grade SDN 114 Bojongkoneng, Cibeunying Bandung classroom. The finding was 77,77% students collaboration actively when did the project. Also by peer rating, 74,09% students argued that their mates in group in good collaboration. In conclusion PjBL type Make a Crossword puzzle have positively influenced to improve students collaboration skill.